Цифрові структурно-літологічні моделі нижньокрейдяних континентальних розсипів ільменіту у верхній палеотечії Лебедин-Балакліївської палеодолини (центральна частина Українського щита) - Крошко, Ю.В. (Геоінформатика, 2016)
Схарактеризовано особливості геологічної будови та ільменітоносності порід фундаменту, кори вивітрювання і нижньокрейдяних відкладів у межах верхньої палеотечії Лебедин-Балакліївської палеодолини. На підставі даних координат, опису свердловин і визначень вмісту ільменіту побудовано цифрові структурно-літологічні моделі нижньокрейдяних континентальних розсипів ільменіту (Бирзуловський, Валуївський, Лип’янський), які відображують характер підошви і поверхні відкладів, потужність продуктивних літотипів та просторовий розподіл вмісту корисного компонента. Приведена характеристика особенностей геологического строения и ильменитоносности пород фундамента, коры выветривания и нижнемеловых отложений в верхнем палеотечении Лебедин-Балаклеевской палеодолины. На основе данных координат, описания скважин и определения содержания ильменита построены цифровые структурно-литологические модели нижнемеловых континентальных россыпей ильменита (Бирзуловской, Валуевской, Липянской), которые отражают характер подошвы и поверхности отложений, мощность продуктивных литотипов и пространственное распределение содержания полезного компонента. Построенные с помощью ГИС-технологий структурно-литологические модели наиболее перспективных россыпей ильменита позволили визуализировать фактический материал, выделить в пределах россыпей участки с наибольшим содержанием ильменита и установить их связь с палеорельефом, определенными микрофациями, литофациями и их мощностью. Россыпи ильменита имеют тесную пространственную и парагенетическую связь с породами кристаллического фундамента основного состава и развитой по ним корой выветривания, содержащих ильменит. С удалением от коренного источника ильменита и коры выветривания продуктивность россыпей снижается. Кроме того, максимальные содержания ильменита приурочены к осевым частям палеодолин и связаны с отложениями русловой микрофации. The purpose of the article is to give a detailed presentation of building digital structural-lithological models of the Apt-lower album continental placers of top paleostreamilmenite of the Lebedyn-Balaklia paleovalleys; based on these coordinates, to describe wells and definitions of the ilmenite content with the view to build digital structural-lithological models of the continental lower Cretaceous placers of ilmenite, which would reflect the character of the sediments roof and surface, the productive capacity of lithotypes, and the spatial distribution of the content of the useful component. Design/methodology/approach. Built with the help of GIS technology, the digital structural-lithological models of the most promising alluvial ilmenite enable us to visualize the actual material, to locate within the areas the placers with the highest content of ilmenite, and to examine their relationship with paleorelief, the identified microfacies, lithofacies, and their capacity. Findings. Within the upper paleostream of the Lebedyn-Balakliiа paleovalleys, we have identified increased ilmenite in crystalline basement rocks (mainly in rocks of basic composition), in their weathering crust, as well as in continental and coastal marine sediments of various ages. The most striking spatial and paragenetic relationship of exogenous ilmenite with endogenous sources (basic rocks) has been is found in the ilmenite weathering crust and continental and coastal sediments of the Lower Cretaceous (the concentration of ilmenite in productive strata decreases with the distance from ilmenite basic rocks and their weathering crust). For prospective areas in the ilmenite continental Lower Cretaceous sediments, we have built digital structural and lithological models to characterize the structure and distribution of productive strata of ilmenite in different facies. The validity of the constructed models was confirmed by comparing them with the actual data of description and testing of wells, which allows us to assess the efficiency of the digital structural and lithologic modeling. Thus, the upper portion of paleostream of the Lebedyn-Balaklia paleovalleys is promising and attractive for investment and development of ore occurrences and deposits of ilmenitewith small. Practical value/implications. Spatial and paragenetic combination of ilmenite basement rocks with ilmenite weathering crusts and the products of their erosion and re-deposition (by Lower Cretaceous continental and coastal-marine formations) permits to select the site as an attractive investment. Digital structural and lithological models of the most promising ilmenite placer built with the help of GIS technology enabled us to visualize the actual material, highlight within the placer the areas with the highest content of ilmenite and clarify their relationship with identified paleoreliefmicrofacies, lithofacies and their capacity. Digital structural and lithological models and their derivatives appear to provide the key basis of support in mining activities.